화병과 A형 행동유형 및 심혈관질환과의 관련성 연구 - 정하룡; Ha Ryong Jeong; 고상백; Sang Baek Koh; 박종구; Jong Ku Park; 유준상; Jun Sang Yu; 공경환; Kyung Hwan Kong; 이재혁; Jae Hyok Lee (동의신경정신과학회지, 2011)
Objectives: The purpose of this research is to investigate the corelationship between Hwa-Byung and type A behavior pattern (TABP), cardiovascular disease. Methods: 637 people participated in the community based cohort study in Wonju City of South Korea from July 2nd to August 30th in 2006. Educated investigators checked up EKG and surveyed Hwa-Byung Diagnostic Interview Schedule(HBDIS), Framingham Type A Pattern Score(FTA score). Collected data were analyzed by the chi-square test & t-test. Results: 1. TABP, Hwa-Byung group was 24(70.6%), non Hwa-Byung group was 288(27.8%) p-value was 0.016. Difference of the two group was valid. 2. FTA score, Hwa-Byung group was 5.77 ± 2.25, non Hwa-Byung group was 4.41 ± 2.30, p-value was 0.002. Difference of the two group was valid. Conclusions: TABP ratio, FTA score was high in Hwa-Byung group compared with non Hwa-Byung group.